O plágio acadêmico refletido no curso de pedagogia, na UFT, campus de Arraias: o caso dos TCC defendidos nos anos de 2017 e 2018 - CHAVES, Ludiane Serafim (Universidade Federal do Tocantins, 2021)
This research involved the search for plagiarism in Course Conclusion Papers (TCC) defended, approved and made available at the Library of the Federal University of Tocantins, Campus de Arraias in 2017 and 2018. The general objective was to verify the presence or absence of plagiarism in the TCC defended in the UFT Pedagogy Course, Campus de Arraias. In total, 87 TCC were analyzed, with 18 defended in 2017 and 69 in 2018, distributed among 28 supervisors among substitute professors, effective members of the College of Pedagogy and other Colleges. The type of plagiarism that was the focus of the research and identified in the TCC were excerpts with direct copies of works by other authors without proper credit. Of the total surveyed, the survey identified 15 TCC with plagiarism distributed among 10 teachers, of these 8 effectives, and of the effective, 5 with more than 10 years of experience. The research concluded that plagiarism is present at an average rate of 18% of the total TCC defended and approved between 2017 and 2018, almost 1/5 of the total, which reflects the need for a deeper discussion about combating academic plagiarism in higher education institutions. As well as the urgent need to improve teachers to qualify themselves in the search for and prevention of plagiarism, as well as the updating of UFT's internal policies and understanding of its interdisciplinary character of action in all periods of the course, especially the initial ones, the in order to provide greater visibility, support, awareness, speed and support in the fight against academic plagiarism.